Analisis Kandungan Kafein Kopi (Coffea arabica) Pada Tingkat Kematangan Berbeda Menggunakan Spektrofotometer UV-VIS - Andi Ilham Latunra; Eva Johannes; Besse Mulihardianti; Ophirtus Sumule (Universitas Hasanuddin, 2021)
A study recently conducted with the title Analysis of caffeine content in arabica coffee (Coffea arabica) based on its maturity level by using Uv-Vis Spectrophotometer. This study aimed to determine the levels of caffeine in Arabica coffee based on its level of maturity, either young, medium and old. Moreover, this study aimed to measure the highest and lowest caffeine levels of Arabica coffe from. Retrieval of young coffee fruit is characterized by green skin fruit, half-old / medium coffee, yellow to orange skin fruit and dark coffee with dark-red skin fruit. The Fruit of Arabica coffee is processed starting from drying, roasting and grinding into coffee grounds. Determination of caffeine content using 2 methods, namely a qualitative test with the parry method and a quantitative test using a UV- Vis spectrophotometer. The results obtained in the qualitative test with the Parry method showed that all three coffee powder samples contained caffeine, this was indicated by a change in color into green. Quantitative test results using UV-Vis spectrophotometer obtained the results of each gram of coffee containing caffeine namely young arabica coffee 11.15 mg or 1.151%, half old / medium arabica 12.85 mg or 1.285 % and old arabica coffee 12.01 mg or 1.201 %. The highest level of caffeine is found in the level of maturity of half-old / moderate coffee and the lowest level of caffeine is found in Arabica coffee with a young age of maturity.